Prevention of hypotension during elective cesarean section with a fixed-rate norepinephrine infusion versus a fixed-rate phenylephrine infusion. Α double-blinded randomized controlled trial. (December 2020) - Theodoraki, Kassiani; Hadzilia, Sofia; Valsamidis, Dimitrios; Stamatakis, Emmanouil
Abstract: Background: Spinal anesthesia for cesarean section can be complicated by hypotension, with untoward effects for both the mother and fetus. Frequently used phenylephrine can lead to baroreceptor-mediated reflex bradycardia. The aim of the present study was to compare a fixed-rate prophylactic norepinephrine infusion to a fixed-rate prophylactic phenylephrine infusion during elective cesarean section under combined spinal-epidural anesthesia. Materials and methods: Eighty-two parturients were randomized to either norepinephrine 4 μg/min or phenylephrine 50 μg/min fixed-rate infusions, starting simultaneously with the administration of the subarachnoid solution. The primary endpoint was the incidence of maternal bradycardia. Maternal hemodynamics at specific timepoints, the incidence of hypotension or hypertension, the requirement for ephedrine or atropine bolus administration as well as the acid-base status and Apgar score of the neonate were recorded. Results: The incidence of bradycardia as well as the requirement for atropine administration was lower in the norepinephrine group (4.8% vs. 31.7%, p = 0.004 and 2.4% vs. 24.3%, p = 0.01, respectively). Fetal pH, and fetal blood glucose concentration were higher in the norepinephrine group (p = 0.027 and 0.019, respectively). No difference in the occurrence of hypotension, hypertension, in the requirement for bolus vasoconstrictive medication or in Apgar scores was demonstrated. Conclusions: A fixed-rate infusion of norepinephrine is as effective in the management of hypotension during regional anesthesia for cesarean section as a fixed-rate infusion of phenylephrine, with the avoidance of phenylephrine-induced bradycardia. The more favourable neonatal acid-base profile of noradrenaline might be due to better maintenance of placental blood flow in the noradrenaline group due to its beta action, while the higher fetal glucose concentration in the same group might result from a catecholamine-stimulated glucose metabolism increase and a β-receptor mediated insulin decrease. Highlights: Hypotension is frequent during spinal anesthesia for cesarean section. Spinal hypotension is commonly managed with phenylephrine. Phenylephrine can lead to baroreceptor-mediated reflex bradycardia. Norepinephrine has been recently introduced in obstetric anesthesia and effectively treats hypotension. A norepinephrine infusion leads to a decreased incidence of bradycardia as compared to phenylephrine.